2021
DOI: 10.26803/ijlter.20.5.1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Standardised Assessment Development Procedure and Algorithms for Computer Adaptive Testing: Applications and Relevance for Fourth Industrial Revolution

Abstract: Teaching and learning have gone online in response to the pandemic, which reveals the need for accurately tailored educational assessments to ascertain the extent to which learning outcomes or objectives are achieved. Computer Adaptive Testing (CAT) is a technology-driven form of assessment that tailors items to a candidate's ability level with empirically proven benefits over the fixed-form computer based test. A systematic review was employed which shows that item bank is a key requirement for CAT and the it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…This, therefore, should ensure that questions that are neither too difficult nor too easy are posed. CAT measures the accuracy of a test score in relation to the duration of the test (Oladele & Ndlovu, 2021).…”
Section: Computerised Adaptive Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…This, therefore, should ensure that questions that are neither too difficult nor too easy are posed. CAT measures the accuracy of a test score in relation to the duration of the test (Oladele & Ndlovu, 2021).…”
Section: Computerised Adaptive Testingmentioning
confidence: 99%
“…Given the increased algorithm flexibility, there is increased security in the administration of the assessment. Furthermore, students engaging in CAT have reported having decreased levels of stress, tiredness, boredom, and anxiety (Oladele & Ndlovu, 2021).…”
Section: Advantages and Disadvantages Of Computerised Adaptive Testsmentioning
confidence: 99%
“…CAT item banks can include both existing paper and pencil items as well as new items, which will maintain psychometric properties while minimizing the cost implications associated with adding additional items (Birdsall, 2011;Thompson & Weiss, 2011). Oladele and Ndlovu (2021) citing Germain (2006), suggested that items should be developed considering content, test domains, and internal consistency, thus ensuring that behavioural measures are valid psychometrically. Most tests are composed of carefully designed items to ensure that they are valid, able to test the subjects intended, and reliable, i.e., they are consistent between administrations.…”
Section: Development Of Item Banks For Catmentioning
confidence: 99%
“…In the IRT model for CAT, only appropriate item pools are used to select items according to examinee ability levels over a series of iterative steps from item selection to stopping criteria until an accurate estimation of theta (θ) level is achieved. An ideal theta level should contain hundreds of items that are uniformly distributed in difficulty, highly discriminating, and have a low guessing parameter for the purpose of effectively assessing the test assembly (Birdsall, 2011;Oladele & Ndlovu, 2021).…”
Section: Eqnmentioning
confidence: 99%
See 1 more Smart Citation